Pengaruh Disiplin, Motivasi Kerja dan Gaya Kepemimpinan terhadap Kinerja Pegawai di Kantor Badan Perencanaan, Penelitian dan Pengembangan Daerah Kabupaten Sigi - Rahmi Talib A. Abbas; Lina Mahardiana; Zakir Muhammad (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2021)
This research revealed the Influence of Dicipline (X1), Work Motivation (X2) and Leadership Style (X3), toward Employee Performance (Y) in Research and Development Planning Agency of Sigi Regency. The purpose of this research is to analyse the influence of Work Dicipline, Motivation and Leadership Style, toward Employee Performance in Research and Development Planning Agency of Sigi Regency. This reseach is classified as a verificative researh and use a survey research design.  Source of data is divided into primary data which are collected through questionnaires and secondary data which is collected from a documentary study which has relation with this research.  The analysis method used in this research is linear and multiple regression analysis which is also supported by a statistical program of SPSS 20.0 version. Result of this research shows that work discipline, work motivation and leadership style has simultaneity significant influence on the employee performance with R square value 0,361 or 31,6%.  While partially this research result is as follows, the discipline has a positive but not significant influence to the employee performance (24,1%), work motivation has a positive and significant influence to the employee performance (63,9%) and leadership style has a positive and significant influence to the employee performance (32,4%). Leader of Research and Development Planning Agency of Sigi Regency must deliver the task to its employee through discipline and responsibility based on regulation so that the employee could give their best service and performance in return.